2022
DOI: 10.3389/fendo.2022.961432
|View full text |Cite
|
Sign up to set email alerts
|

Fasting and stimulated glucagon-like peptide-1 exhibit a compensatory adaptive response in diabetes and pre-diabetes states: A multi-ethnic comparative study

Abstract: BackgroundImpaired secretion of glucagon-like peptide-1 (GLP-1) among Caucasians contributes to reduced incretin effect in type 2 diabetes mellitus (T2DM) patients. However, studies emanating from East Asia suggested preserved GLP-1 levels in pre-diabetes (pre-DM) and T2DM. We aimed to resolve these conflicting findings by investigating GLP-1 levels during oral glucose tolerance test (OGTT) among Malay, Chinese, and Indian ethnicities with normal glucose tolerance (NGT), pre-DM, and T2DM. The association betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…However, very little is known about the effects of endogenous GLP-1 levels in determining the efficacy of DPP-IV inhibition in these individuals. In our previous study (submitted for publication) we have shown that prediabetes and T2D subjects have higher GLP-1 levels compared to normal glucose tolerance ( 30 ). Hence there is a need to determine if this higher GLP-1 levels in these prediabetes and T2D subjects translate into a better efficacy with DPP-IV inhibition.…”
Section: Discussionmentioning
confidence: 96%
“…However, very little is known about the effects of endogenous GLP-1 levels in determining the efficacy of DPP-IV inhibition in these individuals. In our previous study (submitted for publication) we have shown that prediabetes and T2D subjects have higher GLP-1 levels compared to normal glucose tolerance ( 30 ). Hence there is a need to determine if this higher GLP-1 levels in these prediabetes and T2D subjects translate into a better efficacy with DPP-IV inhibition.…”
Section: Discussionmentioning
confidence: 96%
“…Although some studies showed decreased GLP-1 secretion in patients with IGT and T2DM after both OGTT [ 39 , 45 , 46 , 48 ] and MMTT or challenge meals [ 44 , 56 ], others reported an increased [ 42 , 44 , 50 , 55 ] or unchanged [ 47 , 49 , 58 , 69 ] GLP-1 response in the IGT and T2DM groups after OGTT or MMTT/challenge meals. The conflicting nature of the results is also evident from studies reporting increased fasting but decreased meal- or glucose-related GLP-1 concentrations in T2DM [ 38 ] and nonspecified diabetes [ 51 ], or unchanged fasting but reduced early postprandial GLP-1 concentrations in participants with low insulin sensitivity than in those with high insulin sensitivity [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 [ [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] ] provides an overview of the results of the 13 studies included on fasting and peak values of glucose-stimulated GLP-1, the delta between both values, the time at which peak concentration is achieved, GLP-1 concentrations at selected time points, and the AUC or iAUC values (the GLP-1 concentrations measured at all time points are shown in Supplemental Table 2 ). In addition, details of the assays used for GLP-1 measurements are presented.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations